Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Identify a formula for each entry of the matrix $\begin{pmatrix} 1 & 3 \\ 2 & 6 \end{pmatrix}^n$.

It's easy to find a solution by just looking at the first few results: \begin{pmatrix} 7^{n-1} & 3\cdot 7^{n-1} \\ 2\cdot 7^{n-1} & 6\cdot 7^{n-1} \end{pmatrix}

But how would I do it if it wasn't so obvious?

share|improve this question
1  
Diagonalize.${}$ –  Chris Eagle Feb 14 '13 at 11:30
1  
with Cayley-Hamilton theorem –  Mercy Feb 14 '13 at 11:30
6  
If $M = A^{-1}DA$ then $M^n = A^{-1}D^nA$. If $D$ is diagonal, $D^n$ can be easily calculated. –  Alfonso Fernandez Feb 14 '13 at 11:32
1  
Diagonalization is the "standard" way to solve this kind of problems. In your particular case, however, your matrix is equal to $uv^T$, where $u^T=(1,2)$ and $v^T=(1,3)$. Therefore $(uv^T)^n=u(v^Tu)(v^Tu)v^T\cdots u(v^Tu)v^T=(v^Tu)^{n-1}uv^T$. –  user1551 Feb 14 '13 at 11:41
    
Or you can use inducion. For $n=1$ it is clearly true. Now suppose it is true for some natural $n$. And prove that it is true for $n+1$. –  Tomas Feb 14 '13 at 11:43

4 Answers 4

up vote 3 down vote accepted

Fleshing out a little what the comments hint you:

$$\det(tI-A)=\begin{vmatrix}t-1&-3\\-2&t-6\end{vmatrix}=t(t-7)\Longrightarrow$$

the matrix's eigenvalues are $\,0\,,\,7\,$ , and eigenvectors for these values can be found as follows:

$$(1)\,\,\lambda=0:\;\;\;\;\begin{cases}\;\,-x-3y=0\\{}\\-2x-6y=0\end{cases}\;\;\Longrightarrow x=-3y\Longrightarrow\,\,\text{for example}\,\,\binom{3}{\!\!-1}$$

$$(1)\,\,\lambda=t:\;\;\;\;\begin{cases}\;6x-3y=0\\{}\\-2x+y=0\end{cases}\;\;\Longrightarrow y=2y\Longrightarrow\,\,\text{for example}\,\,\binom{1}{2}$$

Form now the matrix

$$P:=\begin{pmatrix}3&1\\\!\!\!-1&2\end{pmatrix}\Longrightarrow P^{-1}=\begin{pmatrix}\frac{2}{7}&\!\!\!-\frac{1}{7}\\{}\\\frac{1}{7}&\;\frac{3}{7}\end{pmatrix}$$

so that

$$P^{-1}AP=\begin{pmatrix}0&0\\0&7\end{pmatrix}=:D$$

And now it is a piece of cake:

$$A^n=\left(PDP^{-1}\right)^n=PD^nP^{-1}\;\;,\;\;\text{and}\;\;\;D^n=\begin{pmatrix}0&0\\0&7^n\end{pmatrix}\ldots$$

share|improve this answer
    
Nice formula for $D^n$ + –  Babak S. Feb 15 '13 at 9:07

Diagonalization works generally, but it's overkill here. Simpler, note that the 2nd row is twice the 1st, which must stay true for $\rm\,A^n\,$ too since $\rm\, vA = (2,-1)A = 0\,$ $\Rightarrow$ $\rm\,vA^n = (vA)A^{n-1}\! = 0.\:$ So

$$\rm \left[\begin{array}{rr}\rm a_{n+1}\!\!\!\! &\rm b_{n+1}\\ \rm 2a_{n+1}\!\!\!\! &\rm 2b_{n+1}\end{array}\!\right] = \left[\begin{array}{cc}1 \!\!&\rm 3\\ 2\!\! &\rm 6\end{array}\!\right] \left[\begin{array}{rr}\rm a_{n}\!\!\!\! &\rm b_{n}\\ \rm 2a_{n}\!\!\!\! &\rm 2b_{n}\end{array}\right]\Rightarrow \begin{array}{ll} \rm a_{n+1}\! = 7 a_n\!= 7^n a_0\! = 7^n\\ \rm b_{n+1}\! = 7 b_n\! = 7^n b_0\! = 3\!\cdot\! 7^n\end{array} \!\Rightarrow A^{\!n+1} \! = \left[\begin{array}{rr}\rm 7^n\!\!\! &\rm 3\!\cdot\! 7^n\\ \rm 2\!\cdot\! 7^n\!\!\!&\rm 6\!\cdot\! 7^n\end{array}\right] $$

share|improve this answer

$$A^2-Tr(A)\cdot A +\det{A}\cdot I_{2}=O_{2}.$$

$$\det{A}=6-6=0.$$

$$A^{2}=Tr(A) \cdot A=7 \cdot A.$$

$$A^{2}=7A.$$ $$A^{3}=7A^{2}=7^{2}A.$$ $$\vdots$$ $$A^{n}=7^{n-1}\cdot A$$

for me, this proof is more simple.

share|improve this answer

I expand the Mercy's idea with Cayley-Hamilton theorem because I like it.

Let $p(\lambda) = \text{det}(A-\lambda I)$ characteristic polynomial of A. Than you can write $\lambda^n = p(\lambda)g(\lambda) + q(\lambda)$, where $\deg(q)<\deg(p)$. By Cayley-Hamilton theorem you get $A^n = q(A)$. So you need only calculate $A^1,..,A^{m-1}$ where $m$ is dimension of matrix.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.